Firmware Remote Update Method for Door Control Unit of PSD - CHEN Qing; YU Qing (机车电传动)
Dual CPU(TMS320F28335, PIC24FJ64GB004) architecture in DCU of PSD was introduced, and method of firmware remote updates for PIC24FJ64GB004 was discussed in detail. The method was proved stable and reliable through experiments, and avoided using the emulator or programmer to update the firmware for the inconvenience, which improved system stability. Because of no depending on the specific processor and a communication medium, this method is fully applicable to other applications.